2002
DOI: 10.1295/polymj.34.529
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Morphologies of Shell Cross-Linked Micelles Based on Commercial Poly(styrene-block-ethylene-co-butene-block-styrene)

Abstract: ABSTRACT:Chloromethyl groups were introduced into the polystyrene (PS) blocks of hydrogenated poly(styreneblock-butadiene-block-styrene) (SEBS) via Friedel-Crafts reaction. The product (SEBS-CH 2 Cl) formed spherical micelles with PS corona and hydrogenated PB core in THF/ethanol (10/9, v/v). Then, the polystyrene corona carrying CH 2 Cl groups was cross-linked by amination with 1,6-hexanediamine as a cross linker. The shell cross-linked micelles showed spherical core-shell structure and were stable in solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…PEG branching in this polymer can be used to create cross-linkable groups in the system to prepare a shell cross-linked micelle system. Thurmond et al [44] and Li et al [45] reported interesting approaches for cross-linking of the micellar shell in order to stabilize the micelles. Thurmond et al [44] prepared micelles from polyvinyl pyridine-b-poly styrene (M n = 52,500 Da) block copolymer, which on self-assembly, forms shell cross-linked knedel-like micelles, which appear to be a hybrid between dendrimers, hollow spheres, latex particles and block copolymer micelles.…”
Section: Micelle-stabilizing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG branching in this polymer can be used to create cross-linkable groups in the system to prepare a shell cross-linked micelle system. Thurmond et al [44] and Li et al [45] reported interesting approaches for cross-linking of the micellar shell in order to stabilize the micelles. Thurmond et al [44] prepared micelles from polyvinyl pyridine-b-poly styrene (M n = 52,500 Da) block copolymer, which on self-assembly, forms shell cross-linked knedel-like micelles, which appear to be a hybrid between dendrimers, hollow spheres, latex particles and block copolymer micelles.…”
Section: Micelle-stabilizing Strategiesmentioning
confidence: 99%
“…Thurmond et al [44] prepared micelles from polyvinyl pyridine-b-poly styrene (M n = 52,500 Da) block copolymer, which on self-assembly, forms shell cross-linked knedel-like micelles, which appear to be a hybrid between dendrimers, hollow spheres, latex particles and block copolymer micelles. Li et al reported similar stabilization of the micelles by cross-linking the shell of the micelles made from a poly(styrene-b-butadiene-b-styrene) polymer [45]. Their approach involved formation of the micelles in aqueous medium and then cross-linking the hydrophobic portion of the micelles using chloromethylation and amination.…”
Section: Micelle-stabilizing Strategiesmentioning
confidence: 99%
“…SO 3 H SIBS with high IEC values has proton conductivities that are comparable to Nafion ® but higher methanol permeabilities . Incorporation of other functionalities (e.g., amination, benzoylation, naphthylation, among others) prior to sulfonation could enhance the properties (i.e., low water uptake, high transport, thermal, and oxidative) of the material and its potential as an alternative PEM . For example, phosphonic acid is another protogenic functionality that could be effective in improving the performance of SO 3 H SIBS due to its higher degree of self‐dissociation and hydrogen bonding, chemical and thermal stability, and lower acidity …”
Section: Introductionmentioning
confidence: 99%
“…Poly(styrene‐b‐(ethylene‐co‐butene)‐b‐styrene) (SEBS) (an aromatic block copolymer similar to SIBS) has been chloromethylated in the past, yielding a material with slightly altered monodispersity that can be used as macroinitiator for grafting via atom transfer radical polymerization (ATRP) . The grafting of copolymers via ATRP have been previously studied .…”
Section: Introductionmentioning
confidence: 99%
“…Thurmond et al [52] prepared micelles from polyvinyl pyridineb-poly styrene (M n = 52,500 Da) block copolymer, which on self-assembly, forms shell cross-linked knedel-like micelles. Li et al reported similar stabilization of the micelles by cross-linking the shell of the micelles made from a poly(styreneb-butadiene-b-styrene) polymer [53] by first preparing micelles in aqueous medium and then cross-linking the hydrophobic portion of the micelles using chloromethylation and amination.…”
Section: Cross-linking the Shellmentioning
confidence: 99%